Ternary g‐C3N4/ZnNCN@ZIF‐8 Hybrid Photocatalysts with Robust Interfacial Interactions and Enhanced CO2 Reduction Performance. Issue 8 (24th January 2020) - Xie, Yi; Zhuo, Yifan; Liu, Shengwei; Lin, Yunan; Zuo, Daren; Wu, Xi; Li, Chuanhao; Wong, Po Keung
Abstract : Carbon dioxide (CO2 ) is one of the main greenhouse gases in the atmosphere and its concentration continues to rise, which has become a global environmental problem. The artificial photosynthesis technology involving the photocatalytic conversion of CO2 to solar fuels is one of the most promising strategies to reduce CO2 and utilize it to produce alternative chemical energy such as methane and methanol. Unfortunately, photocatalytic CO2 reduction performance based on graphitic carbon nitride (g‐C3 N4 ) is usually limited by poor charge separation ability and limited CO2 adsorption ability. Herein, novel ternary g‐C3 N4 /ZnNCN@ZIF‐8 hybrid photocatalysts with robust interfacial interactions via ZnN bonding are constructed by sequential in situ interfacial reactions, to overcome the aforementioned two shortcomings and to enhance photocatalytic CO2 conversion efficiency. Because of the synergetic effects of g‐C3 N4 /ZnNCN interfacial Z‐scheme heterostructuring and surface‐passivated ZIF‐8 grafting in improving light harvesting ability, enhancing CO2 capture capacity, and promoting interfacial charge transfer efficiency, the photocatalytic CO2 reduction activity of novel ternary g‐C3 N4 /ZnNCN@ZIF‐8 hybrid photocatalyst is significantly improved by 104.6%, relative to that of g‐C3 N4 . This study will offer new insights for exploiting novel efficient g‐C3 N4 ‐based hybrid photocatalyst systems for artificial photosynthesis and in modulating the complex photocatalytic processes systematically. Abstract : Ternary g‐C3 N4 /ZnNCN@ZIF‐8 hybrid photocatalysts with robust interfacial interactions via ZnN bonding are constructed by sequential in situ interfacial reactions, to overcome the two shortcomings of g‐C3 N4 photocatalyst regarding poor charge separation ability and limited CO2 adsorption ability, and to enhance photocatalytic CO2 conversion efficiency, due to the synergetic effects of g‐C3 N4 /ZnNCN interfacial Z‐scheme heterostructuring and surface‐passivated ZIF‐8 grafting.